From Political Radicalness to Citizen Participation? Current Reconfigurations of the Breton movement. - Toutous, Jeanne (PARTECIPAZIONE E CONFLITTO, 2020)
This article aims at analyzing the recent mutations of the Breton repertoire of contention. To do so, it proposes to look at the example of an association called "Dibab", which praised participatory democracy by organizing local votes on nationalitarian topics in small Breton towns during the year of 2015. Having a look at the trajectory of Dibab activists shows that many of them had started their militant career years ago, and were familiar to more radical pro-independence organizations. How do these activists have managed to play with different political strategies without losing their ideological frames? How have they expressed different kinds of commitment through their political practices and discourses? Observations, document studies and semi-structured biographical interviews disclose that the construction of a new participatory ideal by radical Breton activists does not prevent them from being multipositioned in the militant field, widening their action spectrum by doing so. That is why the Breton repertoire is better understood as a continuum. Indeed, long term processes and the juxtaposition of different spaces of mobilization must be taken into account in the analysis.